QS. Al-Alaq (3) : Landasan Berpikir Kritis sebagai Kunci Inovasi - Ratnaduhita Nabilah Azzahra; Renaningtyas Putri Lestari; Wayan Mayuda (Jurnal Manajemen dan Pendidikan Agama Islam, 2025)
In the digital era and the Industrial Revolution 4.0 towards Society 5.0, innovation becomes crucial, but many young people are still trapped in consuming information immediately without sufficient analytical skills. The absence of a culture of literacy and reading causes innovation that is only based on imitation. The initial message of Islam "Iqra' wa rabbukal-akram" (Read, and your Lord is Most Gracious) provides a solution, emphasizing that reading is the key to gaining knowledge, broadening your views, and developing critical thinking. Reading includes observing nature, social phenomena, and the signs of God's power, which require reflective thinking. The history of Islamic civilization shows progress triggered by the spirit of "iqra'," which gave birth to famous scholars such as Ibn Sina and Al-Khawarizmi. In the current era of globalization and technological challenges, these values ​​are becoming increasingly crucial. Al-'Alaq 3 serves as an eternal call to develop critical thinking as a moral and spiritual responsibility, linking contemporary innovation with the ability to read critically. This article is intended to analyze QS. Al-'Alaq 3 as the basis of critical thinking in Islam, encourages scientific research and creative expression of gratitude. This study applies qualitative literature methods, which combine Islamic literature and contemporary critical thinking.